THE INFLUENCE OF THE AMOUNT AND PLASTICITY OF FINES ON THE CHARACTERISTICS OF CONSOLID-TREATED GRANULAR MATERIALS - Johanis Paransi, Muhammad
Unbound materials used for subbase and roadbase layers should have a particle size distribution which provides mechanical stability and should have sufficient material passing the 0.425 mm sieve to produce a dense material when compacted. Normally, the maximum allowable plasticity index is 6% and the percentage passing 0.075 mm sieve is limited to achieve the strength requirement, normally specified in terms of CBR value. The main objective of the work described in this thesis was to study, by using Consolid 444 (C444) and Conservex (CX) additives, the possibility of using materials which have a fines content and plasticity index greater than the specified values for subbase or roadbase layers. Eight mixtures with varying amounts of fines and having a high plasticity index were prepared by mixing Galunggung coarse sand and Tanjungsari heavy clay soil. CBR tests were carried out on samples compacted in a 6 inch mold in accordance with AASHTO Designation T180-90; method D. The tests were performed on untreated, uncured mixtures and on mixtures treated with varying amounts of C444 and C444 plus CX and cured for different periods. Dynamic Cone Penetrometer (DCP) tests were performed on some mixtures and a limited study was made of the effect of the additives on permeability. The tests results indicate that the addition of C444 additive increases significantly the CBR value of all mixtures investigated, in particular those having a fines content of 20% or more. The addition of CX additive in mixtures containing C444 is particularly effective in increasing the CBR value of mixtures with 10% fines. The addition of the additive reduces significantly the permeability of the one mixture investigated. From a strength point of view, the use of C444 plus CX upgrades the mixtures with 20% fines from subbase to roadbase quality material.